Implementing an Eye Movement and Desensitization Reprocessing Treatment-Program for Women With Posttraumatic Stress Disorder After Childbirth - Kranenburg, Leonieke W.; Bijma, Hilmar H.; Eggink, Alex J.; Knijff, Esther M.; Lambregtse-van den Berg, Mijke P. (Frontiers in Psychology, 2022)
Purpose: The purpose of this study is to describe the implementation and outcomes of an Eye Movement and Desensitization Reprocessing (EMDR) treatment-program for women with posttraumatic stress disorder (PTSD) after childbirth. Methods: A prospective cohort-study with pre- and post-measurements was carried out in the setting of an academic hospital in the Netherlands. Included were women who gave birth to a living child at least 4 weeks ago, with a diagnosis of PTSD, or severe symptoms of PTSD combined with another psychiatric diagnosis. All received up to 8 sessions of EMDR-therapy. The posttraumatic stress disorder Checklist for DSM-5 was administered before and after treatment. Trauma history was assessed before treatment with the Life Events Checklist for the DSM-5, the Childhood Trauma Questionnaire and the Childbirth Perception Scale. Descriptive statistics were used. Results: Forty-four women were referred, 26 met the inclusion criteria. After treatment, none of the women met the criteria for diagnosis of PTSD after on average 5 weekly sessions of EMDR- therapy. These outcomes are promising, as they were achieved in women with relatively high levels of psychiatric comorbidity (64%) and high rates of previous mental health treatment (80%). Conclusion(s): Implementing an EMDR-treatment program for women with PTSD after childbirth in the setting of an academic hospital is feasible and effective. Key factors for success include a close collaboration between the relevant hospital departments and a thorough case conceptualization addressing the etiology of the PTSD.